Hypothalamic Leptin Gene Therapy Reduces Bone Marrow Adiposity in ob/ob Mice Fed Regular and High-Fat Diets - Lindenmaier, Laurence B.; Philbrick, Kenneth A.; Branscum, Adam J.; Kalra, Satya P.; Turner, Russell T.; Iwaniec, Urszula T. (Frontiers in Endocrinology, 2016)
Low bone mass is often associated with increased bone marrow adiposity. Since osteoblasts and adipocytes are derived from the same mesenchymal stem cell progenitor, adipocyte formation may increase at the expense of osteoblast formation. Leptin is an adipocyte-derived hormone known to regulate energy and bone metabolism. Genetic (e.g., leptin deficiency) and high fat diet-induced (e.g., leptin resistance) obesity are associated with increased marrow adipose tissue (MAT) and reduced bone formation. Short-duration studies suggest that leptin treatment reduces MAT and increases bone formation in leptin-deficient ob/ob mice fed a regular diet. Here, we determined the long-duration impact of increased hypothalamic leptin on marrow adipocytes and osteoblasts in ob/ob mice using recombinant adeno-associated virus (rAAV) gene therapy. In a first study, eight- to ten-week-old male ob/ob mice were randomized into 4 groups: (1) untreated, (2) rAAV-Lep, (3) rAAV-green fluorescent protein (rAAV-GFP), or (4) pair-fed to rAAV-Lep. For vector administration, mice were placed in a Kopf stereotaxic apparatus, and injected intracerebroventricularly with either rAAV-Lep or rAAV-GFP (9 × 107 particles in 1.5 µl). The mice were maintained for 30 weeks following vector administration. In a second study, the impact of increased hypothalamic leptin levels on MAT was determined in mice fed high fat diets. Eight- to ten-week-old male ob/ob mice were randomized into 2 groups and treated with either rAAV-Lep or rAAV-GFP. At 7 weeks post-vector administration, half the mice in each group were switched to a high fat diet for 8 weeks. Wild type (WT) controls included age-matched mice fed regular or high fat diet. Hypothalamic leptin gene therapy increased osteoblast perimeter and osteoclast perimeter with minor change in cancellous bone architecture. The gene therapy decreased MAT levels in ob/ob mice fed regular or high fat diet to values similar to WT mice fed regular diet. These findings suggest that leptin plays an important role in regulating the differentiation of mesenchymal stem cells to adipocytes and osteoblasts. Furthermore, leptin resistance may play a role in the switch from osteoblastogenesis to adipogenesis associated with obesity. However, the results also illustrate that reducing MAT does not necessarily result in increased bone mass.